Erect Penile Dimensions in a Cohort of 778 Middle Eastern Men: Establishment of a Nomogram. (22nd April 2015) - Habous, Mohamad; Tealab, Alaa; Williamson, Ben; Binsaleh, Saleh; El Dawy, Sherif; Mahmoud, Saad; Abdelwahab, Osama; Nassar, Mohammed; Mulhall, John P.; Veale, David; Muir, Gordon
Abstract Introduction Accurate data regarding the size of the erect penis are of great importance to several disciplines working with male patients, but little high‐quality research exists on the subject, particularly in different ethnic groups and for erect penis size. Aim The aim of this study was to create a nomogram of erect penile dimensions in a large sample of Middle Eastern men. Methods A retrospective cohort study of 778 men (mean age 43.7; range 20–82) attending urological outpatient clinics in Saudi Arabia was conducted. Exclusion criteria were age under 18 years, a presenting complaint of small or short penis, Peyronie's disease or complaint of congenital curvature, clinical hypogonadism, and previous penile surgery or trauma. Main Outcome Measures Three erect penile dimensions following induction of erection using intracavernosal injection of Quadrimix. Results Mean patient body mass index (BMI) was 29.09 (standard deviation [SD] 5.76). The mean suprapubic skin‐to‐penile tip erect length was 12.53 cm (SD 1.93); the mean erect length from the symphysis pubis to the penile tip was 14.34 cm (SD 1.86); and the mean erect shaft circumference was 11.50 cm (SD 1.74). A nomogram was constructed and statistical analysis performed, demonstrating a weak negative correlation between BMI and erect penile length measured from the suprapubic skin (r = −0.283, P < 0.000) but not from bone to tip, and a weak negative correlation between age and both erect penile length measurements (skin to tip r = −0.177, P < 0.0005; bone to tip r = −0.099, P = 0.006). Conclusion A nomogram for Middle Eastern men can be used as a standard when advising men with small penis anxiety. The importance of measuring erect size and allowing for infra‐pubic fat interference in measurement is emphasized. We envisage that this tool can be used to educate and reassure concerned men about the size of their penises. Habous M, Tealab A, Williamson B, Binsaleh S, El Dawy S, Mahmoud S, Abdelwahab O, Nassar M, Mulhall JP, Veale D, and Muir G. Erect penile dimensions in a cohort of 778 Middle Eastern men: Establishment of a nomogram. J Sex Med 2015;12:1402–1406.